Observing parallaxical identities of place in architecture – adopting architectural and psychoanalytical approaches to urban fabrics - D'Arcy-Reed, Louis (Journal of Architecture and Urbanism, 2019)
This article analyses the concept of the parallaxical identity within architecture, and its significance in identifying a metaphysical barrier between buildings, urban fabrics, and cognitive understanding. The research focuses and expands upon Slavoj Žižek’s parallax of postmodernist cultural architecture and it’s “zero-institutional” role in marginalising class-struggle and incommensurability between architecture and audience. Interrogating psychoanalytical parallax and architectural concepts of parallax in its history, it explains the determining of a “parallaxical identity of place,” present within cities and as a result of regeneration schemes. Through a design method examining an example of cultural architecture, this article presents a case to integrate psychoanalytical analysis as a useful design methodology within practice. At the end of the article, recommendations are made on how to observe and manage against any potential dissociative or psychological barrier between architecture, environment and community.